Understanding the Consequences of Soil Amendments on Host Selection by a Maize Viral Vector (CicadulinambilaNaudé) (Global Journal of Agricultural Innovation, Research & Development, 2016)
The significance of applying different rates of soil elements on host selection by a viral vector was studied in a confined habitat, to understand the mechanism of host selection by the leafhopper (CicadulinambilaNaudé), a vector of Maize Streak Virus Disease (MSV). Field collected leafhoppers were used in a screen house to assess insect settling preferences by evaluating insect behavior towards host plants, exposed to different rates of nitrogen and phosphorus fertilizers (0, 25, 50 and 75kg/ha.). Analysis of the two elements in the host plant tissues showed significant variation in levels of percent nitrogen (% N: p = 0.031) and phosphorus (% P: p = 0.001). Similarly, a significantly higher number of insects settled on plants treated with a higher rate of nitrogen (21%) and phosphorus (44%), compared to low rates of the same (9% and 28% respectively) (p = 0.019). Host choice by insects was significantly longer phosphorus treated hosts (four days) than nitrogen treated (three days). No significant differences were detected in the analysis of host plants for % neutral detergent fibers, acid detergent fibers, lignin and tannins. However, regression analysis revealed that neutral detergent fibers had significantly negative relationship with nitrogen fertilizer, while and phosphorus showed a negative relationship with lignin. This study showed that fertilizer amendments can critically affect host attack by leafhoppers with amplifications on viral disease transmission.
Keywords: Nitrogen; phosphorus; colonization; maize streak; transmission